Penerapan Media Pembelajaran Geogebra pada Minat Belajar Siswa SMP Al Faqihil Muqoddam - Jufri, Syf Salamah Al; Suriyana, Suriyana; Nizarrahmadi, Nizarrahmadi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to apply GeoGebra learning media and determine the learning interest of Alfaqihil Muqoddam junior high school students. This study uses a quantitative method with a sample of 15 eighth-grade students. Data were collected through observation and a questionnaire on student learning interest. Observation was used to assess the implementation of learning using GeoGebra media, while the questionnaire was used to measure the level of student learning interest in the use of this media. The results of the study indicate that the application of GeoGebra learning media has a positive effect on students' learning interest. This can be seen from the average questionnaire results, which show that 79% of students gave very positive responses. Based on the analysis of learning interest indicators, the results obtained were: enjoyment of 84% (very high category), attention of 96% (very high category), involvement of 72% (fair category), and interest of 66% (fair category). In addition, the implementation of learning with GeoGebra media reached an average of 94.64% and was classified as very good. Thus, the use of GeoGebra has been proven effective in increasing students' interest in learning mathematics at Alfaqihil Muqoddam Junior High School.